The Effect of Compensation, Motivation, and Work Discipline on Employee Performance at PT. Agro Artha Surya with Job Satisfaction as an Intervening Variable - Usu, Idrus; Yakup, Yakup; Lamuda, Ilyas; Rahayu, Leni (LPPPIPublishing, 2024)
The aim of this research is to determine the relationship between the variables of compensation, motivation, and work discipline on the variables of job satisfaction and performance. Data collection methods include observation, questionnaires, and documentation. Using PLS analytical tools, the research results indicate that: 1) Compensation does not have a significant effect on employee performance, 2) Motivation has a positive and significant effect on employee performance, 3) Work discipline does not have a significant effect on employee performance, 4) Job satisfaction has a positive and significant effect on employee performance, 5) Compensation has a positive and significant effect on job satisfaction, 6) Motivation has a positive and significant effect on job satisfaction, 7) Work discipline has a positive and significant effect on job satisfaction, 8) Job satisfaction can mediate the effect of compensation on employee performance, 9) Job satisfaction can mediate the effect of motivation on employee performance, 10) Job satisfaction can mediate the effect of work discipline on employee performance.